Two essays on regional labor markets for the Denver area - Wang, Chiung-Hsia, author; Cutler, Harvey, advisor; Mushinski, David, committee member; Shields, Martin, committee member; Weiler, Stephan, committee member; Kroll, Stephan, committee member (Colorado State University. Libraries, 2011)
Borts and Stein (1964) and Mathur and Song (2000) presented a general theoretical framework regional growth model, which shows regional growth based on labor demand and supply simultaneously. However, most previous empirical work estimated only either the regional demand curve or regional supply curve due to limited data availability, and nearly all of these empirical works use a reduced form model. The first goal is to build a more inclusive data set, including cost of production, output, demographic data, and dynamic externality indices, so a complete structural regional labor market model can be estimated. The second goal is to use this dataset in two applied studies. The first applied study is the impact of building a new stadium in the Denver area, and the second is a dynamic externality study on regional growth in the Denver area. The results show building a stadium in the Denver area had a positive impact on employment on labor demand in the Construction and Professional, Scientific and Technical Services sectors and had a positive impact on labor supply in the Professional, Scientific and Technical, and Accommodation and Food Services sectors. These results differ from previous research. The next chapter examines the various diversity indices and econometric techniques that have been used in previous studies in determining the local economic growth for the Denver area. This study compares the dynamic externality results directly across different econometric specifications in order to shed light on the issues of possibly omitted variables bias, endogeneity, and simultaneous bias issues. In addition, comparing the various diversity indices could show a sensitivity of index choice which may affect policy makers' decisions regarding regional development policy. The results of this study indicate that the choice of diversity index does affect empirical results. Moreover, different econometric techniques provide mixed results for most diversity indices.
Keywords: Denver area; stadium; regional labor market; dynamic externalities